Differences in use of telemedicine integrated into traditional primary health care – a comparative observational study - Pär Eriksson; Maria Randjelovic; Hans Thulesius; Tora Hammar; Stefan Lagrosen; Evalill Nilsson (Scandinavian Journal of Primary Health Care)
Telemedicine in primary health care is expected to address many of the issues currently challenging service delivery. However, the impact and effect will depend on who will use the new technology.Objective The objective of the study was to investigate differences between users and non-users of telemedicine integrated into traditional office-based primary health care.Methods Quantitative registry-based population study in two regions in the southeast part of Sweden (n = 73,486), comparing users with non-users of telemedicine across the variables sex, age, socioeconomic status (SES), morbidity and health care seeking behaviour (HSB). Two study periods of six months were used (September 2019–February 2020 for Region Östergötland, and September 2021–February 2022 for Region Kalmar County) to collect user data. A reference period of 36 months (September 2016–August 2019) was used, to collect data on HSB.Results Users were more often women under the age of 60 and had higher morbidity (measured as resource utilisation) than non-users (p < .001). In contrast, no statistically significant differences were seen between the two groups regarding SES, measured as Care Need Index (CNI). Regarding HSB, a proxy measure (health record entries) showed more entries for users than non-users.Conclusions Our findings suggest that users are more likely to be women and below the age of 60. Likewise, users also tend to have a greater need for health care services compared to non-users, and they seek health care more often compared to non-users. No differences regarding SES were found.